2007
DOI: 10.1038/sj.onc.1210428
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination repair is regulated by domains at the N- and C-terminus of NBS1 and is dissociated with ATM functions

Abstract: The proteins responsible for radiation sensitive disorders, NBS1, kinase ataxia-telangiectasia-(A-T)-mutated (ATM) and MRE11, interact through the C-terminus of NBS1 in response to the generation of DNA double-strand breaks (DSBs) and are all implicated in checkpoint regulation and DSB repair, such as homologous recombination (HR). We measured the ability of several NBS1 mutant clones and A-T cells to regulate HR repair using the DR-GFP or SCneo systems. ATM deficiency did not reduce the HR repair frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…It was previously shown that point mutations in the forkhead-associated domain and deletion of amino acids 682 to 693 on human NBS1, corresponding to the MRE11 binding domain, resulted in a failure to observe MRE11 focus formation following gamma irradiation (31). However, the deletion of amino acids 682 to 693 of human NBS1 resulted in an about threefold decrease in homologous recombination, although NBS1 foci were still formed.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that point mutations in the forkhead-associated domain and deletion of amino acids 682 to 693 on human NBS1, corresponding to the MRE11 binding domain, resulted in a failure to observe MRE11 focus formation following gamma irradiation (31). However, the deletion of amino acids 682 to 693 of human NBS1 resulted in an about threefold decrease in homologous recombination, although NBS1 foci were still formed.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, MRE11/RAD50/NBS1 is localized with PCNA at replication forks 58 and is essential for homologous recombination. 42,59 DSBs induced by irradiation occur outside of active replicons, and the speed at which NBS1 moves throughout the entire nucleus is also compatible with damaged regions being recognized on the principle of rapid diffusion and collision. 60 In a second step, the ATM kinase is activated.…”
Section: Model For the Nbs1 Dependent Dna Damage Responsementioning
confidence: 90%
“…40,41 Loss of the NBS1 FHA domain reduced the interaction between mutant NBS1 and MDC1 as well as the stable interaction between NBS1 and g-H2AX modified chromatin. 40 Although the NBS1 N-terminal region has been reported to be essential for functions including cell survival in response to IR, optimal ATM activation, for the intra-S phase checkpoint and efficient homologous recombination, 11,14,17,34,42 the direct phospho-interaction partner of the NBS1 FHA-BRCT domain remains unclear.…”
Section: Functional Domains Of Nbs1mentioning
confidence: 99%
“…Mouse models recapitulate many of the phenotypes seen in patients with ATM mutations, including tumor predisposition, radiosensitivity, and gonadal dysgenesis (30,33,34). Although some studies using transformed cell lines have reported that ATM is not required for HDR (44), others have suggested that ATM plays a critical role (45,46). ATM has been reported to be necessary for DSB resection to generate Replication protein A (RPA)-coated ssDNA (29), an essential early intermediate in HDR.…”
Section: Discussionmentioning
confidence: 99%